The autotetraploid potato genome provides insights into highly heterozygous species. Issue 10 (1st August 2022) - Wang, Fang; Xia, Zhiqiang; Zou, Meiling; Zhao, Long; Jiang, Sirong; Zhou, Yun; Zhang, Chenji; Ma, Yongzhen; Bao, Yuting; Sun, Haihong; Wang, Wenquan; Wang, Jian
Summary: Potato ( Solanum tuberosum L.) originated in the Andes and evolved its vegetative propagation strategy through short day‐dependent tuber development. Herein, we present a high‐quality, chromosome‐scale reference genome sequence of a tetraploid potato cultivar. The total length of this genome assembly was 2.67 Gb, with scaffold N50 and contig N50 sizes of 46.24 and 2.19 Mb, respectively. In total, 1.69 Gb repetitive sequences were obtained through de novo annotation, and long terminal repeats were the main transposable elements. A total of 126 070 protein‐coding genes were annotated, of which 125 077 (99.21%) were located on chromosomes. The 48 chromosomes were classified into four haplotypes. We annotated 31 506 homologous genes, including 5913 (18.77%) genes with four homologues, 11 103 (35.24%) with three homologues, 12 177 (38.65%) with two homologues and 2313 (7.34%) with one homologue. MLH3, MSH6/7 and RFC3, which are the genes involved in the mismatch repair pathway, were found to be significantly expanded in the tetraploid potato genome relative to the diploid potato genome. Genome‐wide association analysis revealed that cytochrome P450, flavonoid synthesis, chalcone enzyme, glycosyl hydrolase and glycosyl transferase genes were significantly correlated with the flesh colours of potato tuber in 150 tetraploid potatoes. This study provides valuable insights into the highly heterozygous autotetraploid potato genome and may facilitate the development of tools for potato cultivar breeding and further studies on autotetraploid crops.